Assessing sediment quality in Spanish ports using a green alga bioassay - C Morales-Caselles; A Rico; F Abbondanzi; T Campisi; A Iacondini; I Riba; A DelValls (Ciencias Marinas, 2008)
Coastal zones are under environmental pressure due to human activities, and ports are the areas that probably present the highest levels of contaminants in their sediments. In the present study we have combined chemical data and biological effects to determine the sediment quality of six Spanish ports. Trace metals and organic contaminants have been analyzed, and an acute bioassay was carried out in sediment elutriate using the unicellular green alga Dunaliella tertiolecta. The toxicological parameter employed was EC50, which was estimated after exposure to different concentrations of elutriates during 72 h. The development of this alga may be affected when there is a xenobiotic in the environment, and growth inhibition can be quantified and linked to the levels of contaminants in the sediment in order to determine its quality. The results showed that the metals (Cd, Cr, Hg, and Zn) and organic contaminants (PAHs and PCBs) bound to the sediments reduced the normal growth of the alga, but no alterations were detected due to the presence of Cu. The main disadvantage observed was the hormesis produced by the presence of high levels of organic material in the sediment that might hide the toxicity of xenobiotics.